Typification of the plant names described by Nedeljko Košanin from the Balkan Peninsula - Vukojicic, Snezana; Jakovljevic, Ksenija; Djurovic, Sanja; Kuzmanovic, Nevena; Jankovic, Ivana; Stevanovic, Vladimir (Phytotaxa, 2014)
Nedeljko Košanin was one of the most important Serbian botanists from the beginning of the 20th Century. He dedicated most of his life to investigate the flora of Southern Serbia as well as Albania and the Former Yugoslav Republic of Macedonia. Since he was working at the Institute of Botany and Botanical Garden in Belgrade, the majority of his collection is deposited in BEOU. While describing new taxa, in most of his publications he did not indicate the holotype. The present study discusses the lectotypification of 7 names published by Košanin alone, or with his contemporaries.